Direct Binding and Regulation by Fur and HapR of the Intermediate Regulator and Virulence Factor Genes Within the ToxR Virulence Regulon in Vibrio cholerae - Gao, He; Zhang, Jingyun; Lou, Jing; Li, Jie; Qin, Qin; Shi, Qiannan; Zhang, Yiquan; Kan, Biao (Frontiers in Microbiology, 2020)
Cholera toxin (CT) and toxin coregulated pilus (TCP, TcpA is the major subunit) are two major virulence factors of Vibrio cholerae, both of which play critical roles in developing severe diarrhea in human. Expression of CT and TCP is under the tight control of the regulatory cascade known as the ToxR virulence regulon, which is composed of three regulators ToxR, TcpP and ToxT. Besides, their expression is also regulated by the quorum sensing (QS) master regulator HapR and the regulatory protein Fur. Though transcription of tcpP, toxT, and/or tcpA are reported to be regulated by HapR and Fur, to date there are no studies to verify their direct regulations. In the present study, we showed that HapR directly repress the transcription of tcpP and tcpA by binding to their promoter regions, and possibly repress toxT transcription in an indirect manner. Fur directly activated the transcription of tcpP, toxT, and tcpA by binding to their promoters. Taking account of the sequential expression of hapR, fur, tcpP, toxT, and tcpA in the different growth phases of V. cholerae, we deduce that at the early mid-logarithmic growth phase, Fur binds to the promoters of tcpP, toxT, and tcpA to activate their transcription; while at the later mid-logarithmic growth phase, HapR can bind to the promoters of tcpP and tcpA to repress their transcription. Our study reveals the new recognition in the virulence regulatory pathways in V. cholerae and suggests the complicated and subtle regulation network with the growth density dependence.